Solai lignei veneziani in età moderna. Qualche osservazione sulle tecniche e i materiali attraverso un caso di studio - Ceriani Sebregondi, Giulia (Opus Incertum, 2018)
Starting from specific case studies of little transformed buildings, particularly well documented in the archive records, and for which direct observation is possible, more general considerations can be drawn in search of the knowledge that allows us to reconstruct the work site of past centuries. The case study presented is that of the palace erected ex novo in Venice by the doge Leonardo Donà dalle Rose in 1610-12, whose building records allow us to reconstruct in detail the supply system, the types of wood used, the techniques, and the lexicon of early modern Venetian carpentry, including the use of ‘composed beams’. It confirms that, compared to central Italy, in early modern Venice, in almost all cases the single-layered timber structure of the floor remains exposed and uses beams placed very close to each other, thus providing a spatial rhythm to the ceiling and directly supporting a series of timber planks.Venetian buildings, in fact, in order to not overload the foundation ground and to confer some flexibility to the structure, respond to the concept of box-like lightweight structures. In addition to regularity, these slabs, then, also have the advantage of providing a uniform distribution of loads on the masonry, and with their strong joints result in a sufficiently rigid plate that braces the slender walls.